Platelet lysate reduces the chondrocyte dedifferentiation during in vitro expansion: Implications for cartilage tissue engineering. (December 2020) - De Angelis, Elena; Grolli, Stefano; Saleri, Roberta; Conti, Virna; Andrani, Melania; Berardi, Martina; Cavalli, Valeria; Passeri, Benedetta; Ravanetti, Francesca; Borghetti, Paolo
Abstract: In vitro studies have demonstrated that platelet lysate (PL) can serve as an alternative to platelet-rich plasma (PRP) to sustain chondrocyte proliferation and production of extracellular matrix components in chondrocytes. The present study aimed to evaluate the direct effects of PL on equine articular chondrocytes in vitro in order to provide a rationale for in vivo use of PL. An in vitro cell proliferation and de-differentiation model was used: primary articular chondrocytes isolated from horse articular cartilage were cultured at low density under adherent conditions to promote cell proliferation. Chondrocytes were cultured in serum-free medium, 10% foetal bovine serum (FBS) supplemented medium, or in the presence of alginate beads containing 5%, 10% and 20% PL. Cell proliferation and gene expression of relevant chondrocyte differentiation markers were investigated. The proliferative capacity of cultured chondrocytes, was sustained more effectively at certain concentrations of PL as compared to that with FBS. In addition, as opposed to FBS, PL, particularly at percentages of 5% and 10%, could maintain the gene expression pattern of relevant chondrocyte differentiation markers. In particular, 5% PL supplementation showed the best compromise between chondrocyte proliferation capacity and maintenance of differentiation. The results of the present study provide a rationale for using PL as an alternative to FBS for in vitro expansion of chondrocytes for matrix-assisted chondrocyte implantation, construction of 3D scaffolds for tissue engineering, and treatment of damaged articular cartilage. Highlights: Platelet lysate (PL), released by alginate beads, can sustain in-vitro proliferation and differentiation of chondrocytes In cell-based therapies, Platelet lysate (PL) could be used for the in vitro chondrocyte expansion PL 5 to 10% maintains the gene expression pattern of markers typical of mature articular chondrocytes PL could be an alternative to xenogeneic serum by strongly promoting the proliferative potential of horse chondrocytes